Multiobjective Optimization for Multicast Routing in Overlay Networks using Evolutionary Algorithms (2008)
Multicast plays a very important role to support a new generation of applications. At present and for different reasons, technical and non-technical, IP multicast has not been fully adopted on the Internet. During the last years, an area of active research is to implement this type of traffic from the perspective of the application level, where multicast functionality is not the responsibility of the routers but of the hosts, which is known as Multicast Overlay Network (MON). This article considers routing in MON as a Multi-Objective Optimization (MOP) problem where two functions are optimized: 1) the total end-to-end delay of the multicast tree, and 2) maximum link utilization. The simultaneous optimization of these two functions is a complete NP problem and to solve it it is proposed to use Multiobjective Evolutionary Algorithms (MOEA), specifically NSGAI